CASE REPORTSRepair of a postinfarction ventricular septal defect through the aortic opening – a case report - Tułecki, Łukasz; Mizerski, Jeremi; Bródka, Jarosław (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2013)
Repairing postinfarction ventricular septal defects located in the posterobasal part of the septum is one of the most demanding procedures in cardiac surgery. In the presented case of a 63-year-old patient, an approach through the aortic valve opening was applied. The method was adopted from the field of congenital heart surgery. The presented technique may be a good alternative to the widely used approach employing posterior ventriculotomy.